Related Articles

# Class 11 RD Sharma Solutions – Chapter 30 Derivatives – Exercise 30.4 | Set 3

• Last Updated : 16 May, 2021

### Question 21. Differentiate (2x2 – 3) sin x with respect to x.

Solution:

We have,

=> y = (2x2 – 3) sin x

On differentiating both sides, we get, On using product rule we get,   ### Question 22. Differentiate with respect to x.

Solution:

We have,

=> y = On differentiating both sides, we get, On using product rule we get,    ### Question 23. Differentiate with respect to x.

Solution:

We have,

=> y = On differentiating both sides, we get, On using product rule we get,      ### Question 24. Differentiate with respect to x.

Solution:

We have,

=> y = On differentiating both sides, we get, On using product rule we get,     ### Question 25. Differentiate with respect to x.

Solution:

We have,

=> y = On differentiating both sides, we get, On using product rule we get,       ### Question 26. Differentiate (ax + b)n (cx + d)m with respect to x.

Solution:

We have,

=> y = (ax + b)n (cx + d)m

On differentiating both sides, we get, On using product rule we get,    ### Question 27. Differentiate in two ways, using product rule and otherwise, the function (1 + 2 tan x) (5 + 4 cos x). Verify that the answer are the same.

Solution:

We have,

=> y = (1 + 2 tan x) (5 + 4 cos x)

On using product rule we get,  = 10 sec2 x + 8 cos x sec2 x − 4 sin x − 8 sin x tan x

=    = 10 sec2 x + 8 cos x − 4 sin x

By using an alternate method, we have,   On using chain rule, we get,

= 0 − 4 sin x + 10 sec2 x + 8 cos x

= 10 sec2 x + 8 cos x − 4 sin x

Hence proved.

### (i) (3x2 + 2)2

Solution:

We have,

=> y = (3x2 + 2)2

On using product rule we get,  = 12x (3x2 + 2)

= 36 x3 + 24x

By using an alternate method, we have, On using chain rule, we get,

= 36 x3 + 0 + 24 x

= 36 x3 + 24x

Hence proved.

### (ii) (x + 2)(x + 3)

Solution:

We have,

=> y = (x + 2)(x + 3)

On using product rule we get, = (x+3)(1)+(x+2)(1)

= x + 3 + x + 2

= 2x + 5

By using an alternate method, we have, On using chain rule, we get,

= 2x + 5

Hence proved.

### (iii) (3 sec x − 4 cosec x) (−2 sin x + 5 cos x)

Solution:

We have,

=> y = (3 sec x − 4 cosec x) (−2 sin x + 5 cos x)

On using product rule we get, = (−2 sin x + 5 cos x) (3 sec x tan x + 4 cot x cosec x)+ (3 sec x − 4 cosec x) (−2 cos x − 5 sin x)

= −6 sin x sec x tan x − 8 sin x cot x cosec x + 15 cos x sec x tan x  + 20 cos x cot x cosec x − 6 sec x cos x − 15 sec x sin x + 8 cosec x cos x + 20 cosec x sin x

= −6 tan2 x − 8 cot x + 15 tan x + 20 cot2 x − 6 − 15 tan x + 8 cot x + 20

= − 6 − 6 tan2 x + 20 cot2 x + 20

= −6 (1 + tan2 x) + 20 (cot2 x + 1)

= −6 sec2 x + 20 cosec2 x

By using an alternate method, we have,   On using chain rule, we get,

= −6 sec2 x − (−20 cosec2 x)

= −6 sec2 x + 20 cosec2 x

Hence proved.

Attention reader! All those who say programming isn’t for kids, just haven’t met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12.

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

My Personal Notes arrow_drop_up